SARS-CoV-2 D614G spike mutation increases entry efficiency with enhanced ACE2-binding affinity - Ozono, Seiya; Zhang, Yanzhao; Ode, Hirotaka; Sano, Kaori; Tan, Toong Seng; Imai, Kazuo; Miyoshi, Kazuyasu; Kishigami, Satoshi; Ueno, Takamasa; Iwatani, Yasumasa; Suzuki, Tadaki; Tokunaga, Kenzo (Nature communications, 2021)
The causative agent of the COVID-19 pandemic, SARS-CoV-2, is steadily mutating during continuous transmission among humans. Such mutations can occur in the spike (S) protein that binds to the ACE2 receptor and is cleaved by TMPRSS2. However, whether S mutations affect SARS-CoV-2 cell entry remains unknown. Here, we show that naturally occurring S mutations can reduce or enhance cell entry via ACE2 and TMPRSS2. A SARS-CoV-2 S-pseudotyped lentivirus exhibits substantially lower entry than that of SARS-CoV S. Among S variants, the D614G mutant shows the highest cell entry, as supported by structural and binding analyses. Nevertheless, the D614G mutation does not affect neutralization by antisera against prototypic viruses. Taken together, we conclude that the D614G mutation increases cell entry by acquiring higher affinity to ACE2 while maintaining neutralization susceptibility. Based on these findings, further worldwide surveillance is required to understand SARS-CoV-2 transmissibility among humans. SARS-CoV-2 D614G spike protein mutation is one of the predominant circulating vital mutants. Here, Ozono et al. demonstrate that D614G mutation increases in vitro cell entry by acquiring higher affinity to ACE2.